Alcalóides bioativos e fenólicos de Hippeastrum solandriflorum (Lindl.) - Amaryllidaceae - Carvalho, Kaline Rodrigues (2014)
This work describes the phytochemical study of Hippeastrum solandriflorum(Amaryllidaceae)aiming the isolation and structural elucidation of new bioactive compounds, as well as its pharmacological investigation. The chemical investigation realized with the EtOH extract from bulbs, through chromatographic methods, including HPLC (reverse phase), resulting inthe isolation of ten compounds: a furan derivative: 5-(hydroxymethyl)furan-2-carbaldehyde(HS-1), two phenolic derivatives: piscidic acid (HS-2), eucomic acid (HS-3), and seven isoquinoline alkaloids: narciclasin ( HS-4), 2α-hydroxypseudolycorin (HS-5), 10α-hydroxy homolycorin (HS-6), galantamin (HS-7), sanguinin (HS-8),N-oxid galantamin (HS-9) andnarcissidin (HS10). The alkaloids (HS-5) and (HS-6) are being reported for the first time inthe literature, while the other ones have been isolated for the first time in the investigated species. The structures of all isolated compounds were determined based on spectrometricmethods (IR, HRMS, NMR 1H and13C–1D and 2D), besides comparison with published data. The cytotoxic potential of all alkaloids were evaluated against several tumor cell lines:colon (HCT-116), leukemia (HL-60), ovary (OVCAR-8) and brain (SF-295) showing IC50ranging from 0.01 to 35.7 μM.